Impact of siRNA transfection on tumor development under experimental pathology of thyroid gland - Zaporozhan, V.M.; Maryniuk, G.S.; Kholodkova, O.L.; Bubnov, V.V.; Andronov, D.U. (Вiopolymers and Cell, 2013)
Aim. To assess the impact of siRNA transfection on the tumor development under experimental pathology of the thyroid gland. Methods. Experiments were performed on rats weighing 180 ± 20 g, which were divided into five groups: IA and IB – animals with simulated hypo- and hyperthyroid states and transplanted Guerin’s carcinoma; IIA and IIB – animals with simulated hypo- and hyperthyroid states and transplanted Guerin’s carcinoma in combination with siRNA transfection; III – control group with transplanted Guerin’s carcinoma in combination with siRNA transfection. Orthogonal dimensions of the tumor were measured. Histological and immunohistochemical researches of tumor samples were performed. Results. It has been shown that the inhibitory effect of short interfering RNA is realized to a greater extent in the hypothyroid state, indicating an important role of thyroid hormones in the regulation of expression of genes that control the cell cycle. We discuss a possible dependence of necrobiotic processes prevalence and characteristic changes in the blood vessels on the effects of thyroid hormones on angiogenesis and proliferative processes. Conclusions. siRNA trasfection leads to inhibition of tumor growth in animals with both hypo- and hyperthyroidism, but it is more pronounced at hypothyroidism. Мета. Оцінити вплив трансфекційно введеної siРНК на розвиток пухлини за умов експериментальної патології щитоподібної залози. Методи. Експерименти виконували на самицях щурів масою 180 ± 20 г. Тварин розділено на п’ять груп: IA і IБ – щури з модельованими гіпо- і гіпертиреозом та перевитою карциномою Герена, IIA і IIБ – з модельованими гіпо- і гіпертиреозом та перевитою карциномою Герена у комплексі з трансфекційно введеною siРНК, ІІІ – з перевитою карциномою Герена у комплексі з трансфекційно введеною siРНК. Вимірювали ортогональні розміри пухлини. Проводили гістологічні та імуногістохімічні дослідження зразків пухлини. Результати. Показано, що інгібувальний вплив коротких інтерферуючих РНК більшою мірою проявляється за гіпотиреоїдного стану, що свідчить про важливу роль гормонів щитоподібної залози у регуляції експресії генів, контролюючих клітинний цикл. Обговорюється ймовірність залежності переважання некробіотичних процесів та характерних змін у судинах від дії тиреоїдних гормонів на ангіогенез і проліферативні процеси. Висновки. Трасфекція siРНК призводить до пригнічення пухлинного росту у тварин як з гіпо-, так і з гіпертиреозом, проте активніше цей процес протікає при гіпотиреоїдному стані. Цель. Оценка влияния трансфекционно введенной siРНК на развитие опухоли в условиях экспериментальной патологии щитовидной железы. Методы. Эксперименты проводили на самках крыс массой 180 ± 20 г. Животных разделили на пять групп: IA и IБ – крысы с моделированными гипо- и гипертиреозом и перевитой карциномой Герена, IIA и IIБ – с моделированными гипо- и гипертиреозом и перевитой карциномой Герена в комплексе с трансфекционно введенной siРНК, III – контрольная группа с перевитой карциномой Герена в комплексе с трансфекционно введенной siРНК. Измеряли ортогональные размеры опухоли. Осуществляли гистологические и иммуногистохимические исследования образцов опухоли. Результаты. Показано, что ингибирующее влияние коротких интерферирующих РНК в большей степени проявляется при гипотиреоидном состояния, что указывает на важную роль гормонов щитовидной железы в регуляции экспрессии генов, контролирующих клеточный цикл. Обсуждается вероятность зависимости преобладания некробиотических процессов и характерных изменений в сосудах от влияния тиреоидных гормонов на ангиогенез и пролиферативные процессы. Выводы. Трансфекция siРНК приводит к угнетению опухолевого роста у животных как с гипо-, так и с гипертиреозом, однако более активно этот процесс протекает при гипотиреоидного состоянии.